Integrated Payment System to Improve Financial Management Using Payment Gateway - Muhamad Rico Aditya Prayoga; Suhirman (INOVTEK Polbeng - Seri Informatika, 2024)
This research focuses on developing an integrated payment system to improve the efficiency and transparency of financial transaction management. The system integrates a payment gateway that allows real-time validation of transactions and supports various payment methods such as bank transfers, digital wallets, and QRIS. The development of this system uses Waterfall methodology to provide flexibility in responding to changing user needs, and utilizes technologies such as the Laravel framework for web development and MySQL as a database, and Flutter for mobile applications used by members of the organization. The implementation of this system aims to overcome inefficiencies in the manual transaction process and reduce the potential for recording errors or misuse of funds. The development of this system follows a structured process, from needs analysis to system testing and evaluation. The results show that the integrated payment system successfully improves transaction management by automating payment validation and providing real-time reporting.